PENGEMBANGAN BAHAN AJAR MAHĀRAH AL-KALĀM BERBASIS USLŪB AL-QUR’ĀN - Syaifudin Syaifudin (Fakutas Tarbiyah Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2020)
Teaching materials are one of the most urgent tools to support the teaching and learning process, without teaching materials the teaching and learning process will not be effective. Currently in schools, teaching materials are available that can be purchased directly from sellers or publishers, but after a close look at many teaching materials that are not yet in accordance with the ideal preparation criteria, it has been proven that teaching materials in Indonesian subjects contain pornographic content. It was also found that Arabic teaching materials contained vocabulary that were not suitable to be taught to students, such as the word